Tax Reforms and Tax Yield in Nigeria - Ebi, Bassey Okon; Ayodele, Oluwafemi (International Journal of Economics and Financial Issues, 2017)
This study estimates elasticity and buoyancy of various tax components as well as the impact of tax reforms on tax components in Nigeria between 1981 and 2014. Error correction mechanism (ECM) technique was employed in analyzing the data. The results revealed that: All the tax components were inelastic, there was a general improvement in post-reformed tax elasticities ranging from 0.199 to 1.28 with petroleum profit tax and the total tax revenue having coefficients >1, values of tax buoyancies were all positive and <1, with post reform samples buoyancies being greater than that of common samples ranging from 0.13 to 0.93, tax reform was further confirms to improve tax revenues by positive and significant coefficients of the dummies. Based on the findings, the study recommended that: Government should diversify the economy for more development as well as strengthening tax reforms in order to increase overall tax revenue. Keywords: Tax Reforms, Tax Elasticity, Tax Buoyancy JEL Classification: H250